Determination of the presence of the fungicide Chlorothalonil in drinking water from communities in Costa Rica using High Resolution Liquid Chromatography (HPLC) - Rojas-Alvarado, Priscilla (2025)
In this study, a qualitative analysis was carried out to determine the presence of the compound chlorothalonil; recognized for its fungicidal properties, in samples of drinking water coming from both the ASADAS or aqueducts as well as from homes located in the communities of Cipreses, Cirrí, Palmira, Escobal and San Juan de Grecia in Costa Rica. The research focused on evaluating the possible contamination of this vital resource by this chemical compound. To carry out this analysis, high-performance liquid chromatography (HPLC) was implemented, based on the methodology established by Gallardo (2020), which allowed precise and qualitative detection of chlorothalonil in the samples examined. Among the results obtained, the presence of chlorothalonil was verified in four of the samples analyzed. However, it is crucial to highlight that the concentrations found were not high enough to be precisely quantified, suggesting the existence of only traces of this compound in the drinking water studied. Although these traces did not reach quantifiable levels, it is important to emphasize that even small amounts of chlorothalonil can have negative implications for human health in the long term. Therefore, these findings evidence the need for continued surveillance and preventive measures to ensure the quality and safety of the drinking water supply in these communities.